Τεκμήρια της καθημερινής ζωής στο βενετικό Αιγαίο. Τα μεταλλικά ευρήματα των ανασκαφών στο Επάνω Κάστρο της Άνδρου (13ος – 17ος αιώνας) - ΜΠΑΡΜΠΑΡΙΤΣΑ Ελένη (Byzantina Symmeikta, 2019)
BYZANTINA SYMMEIKTA 29 (2019), 141-194 194 Evidence of Everyday Life in the Venetian Aegean: The Metal Finds of the Excavations in Epano Kastro of Andros (13th–15th centuries) Epano Kastro (Upper Castle) is located on the southeastern part of the island of Andros and was built by the Venetian sovereigns after 1205 (fig. 1). During the period 2004-2010 a research excavation into preeminent parts of the castle was organized by the University of Athens and headed by Assistant Professor Eleni Deliyianni-Doris (fig. 2). The metal finds, mainly from copper alloys and iron, were serving the practical needs of the inhabitants. Based on the archaeological context and mainly on the subsidiary monetary finds, most of them date back to the period of the Venetian rule on the island (1205-1566). They include: lockers (cat.: 1-7, fig.3), keys (cat.: 8-9, fig. 4), revetments (cat.: 10-11, fig. 5), lighting devices (cat.:12-15, fig. 6), fragments of vessels (cat.: 16-26, fig. 7), knives (cat.: 27-31, fig.8), utensils for spinning and sewing (cat.: 32-35, fig. 9), crossbow arrowheads(cat.: 36-39, fig. 10), firearm shots (cat.: 40-42, fig. 10), parts of horseshoes(cat.: 43-44, fig. 11), sockets (cat.: 45-49, fig. 12) and miscellaneous metal components (cat.: 50-54), including iron nails (fig. 13).